Desain Beton High Early Strength (HES) dengan Campuran Superplasticizer - Fendria, Riki; Irwan, Irwan; Sumantri, Ahmad (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2024)
High initial strength concrete technology is increasingly developing to meet modern projects requiring fast-hardening concrete. This research highlights the role of superplasticizers in achieving high initial strengths. Superplasticizers, and chemical additives, reduce water, accelerate hardening, and simplify concrete work. The compressive strength test method on cylindrical specimens was carried out at the age of 3, 7, and 28 days. Using 250 ml of superplasticizer per sack of cement, with water reduced by 40%, can achieve the quality of concrete f'c 25 MPa at 28 days old. The results showed that concrete with superplasticizer had higher initial compressive strength, increasing by 31.49% in 3 days, and 18.84% in 7 days compared to normal concrete. However, at 28 days old, compressive strength tends to be the same as normal concrete.